The Meeting Of Two Cultures In Laura Fitzgerald's Veil Of Roses Novel (2007): A Sociological Perspective - Kharisma, Pika Ayu; , Dr. M. Thoyibi, M.S; , Titis Setyabudi, S.S., M.Hum (2013)
This research is proposed to analyze how the meeting of two cultures in Laura Fitzgerald's Veil of Roses novel 2007 by Sociological Perspective. The objectives of the study are (1) to analyze the meeting of two cultures in Laura Fitzgerald's Veil of Roses novel (2007) based on its structural elements, (2) to analyze the meeting of two cultures in Laura Fitzgerald's Veil of Roses novel (2007) based on sociological perspective, (3) to describe the characterictics of two cultures in Veil of Roses novel, (4) to describe the meeting of two culture portrayed in Veil of Roses and (5) to analyze the necessary of Laura Fitzgerald to address the meeting of two cultures. The type of this research is qualitative research. The researcher uses two data resources namely primary and secondary data source. The primary data source is Veil of Roses novel by Laura Fitzgerald, and the secondary data sources are books or any information related to the meeting of two cultures that support the sociological perspective. The method of collecting data in this research is library research and the technique of analysing data is descriptive technique. The structural analysis shows that in this novel Laura Fitzgerald delivers a theme that the meeting of two cultures may result in the indentity confusion. The sociological analysis suggest that there is a close relationship between the production of this novel, Veil of Roses, and the social realities of American society in the end of the twentieth century and the beginning of the twenty-first century.